Promoting mealtime function in people with dementia: A systematic review of studies undertaken in residential aged care. (August 2019) - Fetherstonhaugh, Deirdre; Haesler, Emily; Bauer, Michael
Abstract: Background: Dementia is one of the most prevalent conditions in older adults in residential aged care. Dementia has a significant impact on a person's ability to eat, drink and participate in mealtime activities. Dementia impacts memory, appetite, gross and fine motor skills, communication skills, mood and social behaviours, all of which can decrease the person's ability to engage in a meal. Objectives: The objective was to review the literature on strategies to promote mealtime function in people with dementia living in residential aged care and assess their effectiveness. The review considered studies reporting outcome measures that related to nutritional status, communication, behaviour and eating skills and ability. Design: Systematic review using the Joanna Briggs Institute review methods. Data sources: Seven databases (MEDLINE, CINAHL, Cochrane Database of Systematic Reviews, EMBASE, Current Contents, PsycINFO and Allied and Complementary Medicine Database) were searched for research published 2000–2017 in English. Eligible studies included quantitative studies reporting a mealtime intervention delivered to people with dementia in residential aged care compared with standard care reporting nutritional, behavioural or functional outcomes, including observation studies with no comparator. Review methods: Studies were screened and independently appraised by two reviewers using Joanna Briggs Institute (JBI) critical appraisal tools based on study design. Data was extracted from eligible studies using JBI extraction tables that assess study design, population characteristics, intervention and comparator, outcome measures and findings. Results related to mealtime function were tabulated and reported in narrative format. Results: 136 studies were identified, of which 20 were eligible for inclusion. Studies reported strategies related to: food presentation; meal styles; environment adaptations; skills training; music therapy and animal-assisted therapy. Outcomes included measures of nutritional status, communication and behavioural and psychological symptoms of dementia. Low quality evidence suggested that playing music and introducing fish to the dining room may improve the food intake of people with dementia by a small amount. Montessori and spaced retrieval programs also demonstrated some positive impact on eating skills and nutritional intake. Animal-assisted therapy also demonstrated small statistically significant improvements in weight and body mass index. Conclusion: There is insufficient evidence to highly recommend any specific intervention to improve mealtime functional ability in people with dementia. Further research is required through robust study designs using valid and reliable outcome measures to demonstrate clinically significant effects for mealtime interventions.